2019 IEEE International Conference on Artificial Intelligence and Virtual Reality (AIVR) 2019
DOI: 10.1109/aivr46125.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Analytics of Large Dynamic Networks via Overview and Detail Navigation

Abstract: Analysis of large dynamic networks is a thriving research field, typically relying on 2D graph representations. The advent of affordable head mounted displays however, sparked new interest in the potential of 3D visualization for immersive network analytics. Nevertheless, most solutions do not scale well with the number of nodes and edges and rely on conventional fly-or walk-through navigation. In this paper, we present a novel approach for the exploration of large dynamic graphs in virtual reality that interw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Büschel et al [10] have compared the suitability of different edge styles in AR. Others have investigated possibilities of novel interaction design for those environments [1,20,28,34,52]. In terms of interaction, our work is most closely related to the works of Alper et al [1], Kotlarek et al [34], and Sorger et al [52].…”
Section: D Network Visualizationmentioning
confidence: 82%
See 1 more Smart Citation
“…Büschel et al [10] have compared the suitability of different edge styles in AR. Others have investigated possibilities of novel interaction design for those environments [1,20,28,34,52]. In terms of interaction, our work is most closely related to the works of Alper et al [1], Kotlarek et al [34], and Sorger et al [52].…”
Section: D Network Visualizationmentioning
confidence: 82%
“…Others have investigated possibilities of novel interaction design for those environments [1,20,28,34,52]. In terms of interaction, our work is most closely related to the works of Alper et al [1], Kotlarek et al [34], and Sorger et al [52]. Their proposed interaction techniques have inspired us to build on top of the ideas of overview and detail and stereoscopic highlighting.…”
Section: D Network Visualizationmentioning
confidence: 91%
“…The VRige platform [299] permits social network interactions to be explored in an immersive virtual environment. The VR-based framework of Sorger et al [300] provides two navigation modes, overview exploration and immersive detail analysis, to analyze large dynamic networks. Looking ahead, the new field of cross-virtuality [301] has the goal of seamlessly integrating and transitioning among conventional 2D visualizations, augmented reality, and virtual reality; such integrative implementations have not yet been explored for the analysis of OSNs, and these represent an interesting future direction.…”
Section: Discussionmentioning
confidence: 99%
“…count scalability issues in graph drawing, interaction techniques and collaborative visual analysis among the main challenges [vLKS*11]. It has been shown that immersive technologies can facilitate an interactive and efficient visualization of networks [SWKA19, KMLM16, KKM*20]. However, visualization and exploration of networks with immersive technology is underutilized due to various technical, complexity‐ and visualization‐related reasons.…”
Section: Motivationmentioning
confidence: 99%